Factors contributing high-rise residential overhang (district of Kinta) / Nur Atikah Mustapha - Mustapha, Nur Atikah (2023)
Perak has been ranked fifth in terms of residential overhang, with 2,611 unsold units. Among the district in Perak, Kinta has the highest number of residential overhangs, specifically with 1,369 unsold high-rise units. Property overhang occurs when a property has obtained a Certificate of Fitness for Occupation (CFO/CCC) or Temporary Fitness Certificate for Occupation, but remains unsold for at least nine months despite being actively advertised. The main objective of this research is to identify the factors that contribute to high-rise residential overhang in the district of Kinta. Qualitative methods, specifically structured interviews, were utilized, involving experienced housing development managers from the sales and marketing division in Kinta, Perak. The findings from the interview sessions revealed that housing prices were identified as the primary factor contributing high-rise residential overhang in Kinta, followed by unattractive locations. The result will be useful to the government, developer and future researcher in order to overcome the overhang issues in district of Kinta, Perak.